Przejściowa hypotonia jako czynnik prognostyczny po operacji sklerektomii głebokiej łączonej z fakoemulsyfikacją - Rękas, Marek; Siemiątkowska, Anna; Stankiewicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To determinate the influence of hypotonia on the effectiveness of phacoemulsification and deep sclerectomy performed simultanously with the SK-gel implant in 15 months follow up. Material and methods: The retrospective analysis comprised group I (IOP ≤ 6 mm Hg) – 50 eyes and group II (IOP > 6 mm Hg) – 75 eyes. Uncontrolled primary open-angle glaucoma and coexisting cataract were the indication. DBCVA, IOP, anterior segment and eye fundus were assessed as well as the number of antiglaucoma medications. The patients were examined on the first and the seventh day as well as at 1, 3, 6, 12 and 15 months. IOP ≤ 12.15 and 18 mm Hg was accepted as surgical success criterion. T - Student test was used in statistical analysis and variance was analysed. The survival analysis was worked out with Kaplan-Meier method. Results: After 15 months the decrease of mean IOP was obtained in group I by 35.9% (p< 0.05) and in group II by 33.5% (p< 0.05). There were no statistical differences between the number of the applied antiglaucoma medications in the investigated groups. Finally, a qualified surgical success was obtained for the criterion ≤ 18 mmHg in 97.7% of cases in group I and in 87.9% in group II (p= 0.013). For the criterion ≤ 15 mm Hg – in group I 84.3% and in group II 66.4% (p< 0.001), whereas for the criterion ≤ 12 mm Hg respectively in group I 41.2% and in group II 39.3% (p = 0.015). DCBVA 15 months after the surgery was 0.84 ± 0.24 in group I and 0.71 ± 0.25 in group II. At the end of the follow up no significant differences of DBCVA were found between the investigated groups (p> 0.05). Conclusions: Hypotonia is an important positive prognostic factor in the first 24 h after surgery in the case of phacoemulsification, performed at the same time with deep sclerectomy.